Temporal dynamics of attentional selection in adult male carriers of the fragile X premutation allele and adult controls - Wong, Ling M.; Tassone, Flora; Rivera, Susan M.; Simon, Tony J. (Frontiers in Human Neuroscience, 2015)
Carriers of the fragile X premutation allele (fXPCs) have an expanded CGG trinucleotide repeat size within the FMR1 gene and are at increased risk of developing Fragile X-associated Tremor Ataxia Syndrome (FXTAS). Previous research has shown that male fXPCs with FXTAS exhibit cognitive decline, predominantly in executive functions such as inhibitory control and working memory. Recent evidence suggests fXPCs may also exhibit impairments in processing temporal information. The attentional blink (AB) task is often used to examine the dynamics of attentional selection, but disagreements exist as to whether the AB is due to excessive or insufficient attentional control. In this study, we used a variant of the AB task and neuropsychological testing to explore the dynamics of attentional selection, relate AB performance to attentional control, and determine whether fXPCs exhibited temporal and/or attentional control impairments. Participants were adult male fXPCs, aged 18--48 years and asymptomatic for FXTAS (n = 19) and age-matched male controls (n = 20). We found that fXPCs did not differ from controls in the AB task, indicating that the temporal dynamics of attentional selection were intact. However, they were impaired in the letter-number sequencing task, a test of attentional control. In the combined fXPC and control group, letter-number sequencing performance correlated positively with AB magnitude. This finding supports models that posit the AB is due to excess attentional control. In our two-pronged analysis approach, we contribute to the theoretical literature in controls by extending the AB literature, and we enhance our understanding of fXPCs by demonstrating that at least some aspects of temporal processing may be spared.